2015
DOI: 10.4172/2167-7182.1000232
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Markers of Glucose and Insulin Function and Cognitive Function in Healthy African American Elders

Abstract: Background Glucose and insulin are important moderators of cognitive function. African Americans have poorer glycemic control across the glycemic spectrum and are at increased risk for type 2 diabetes and poor cognitive health. It is unclear which glucoregulatory markers predict cognitive function in this at-risk population. The purpose of this study was to examine the association between cognitive function and common markers of glucoregulation in non-diabetic African Americans elders. Methods Thirty-four, c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The origin of cerebral atrophy in lemurs has been explored in previous studies and a relationship between atrophy and intracellular amyloid deposition has been suggested [ 33 ], but this study was based on few animals. In humans, IFG is related to poor cognitive performance and to atrophy of hippocampus [ 16 17 , 19 , 34 ]. We thus assessed whether these parameters could be linked to atrophy in lemurs and found that it is probably the main factor leading to pathologic hippocampal/ septal atrophy and the associated cognitive alterations in lemurs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The origin of cerebral atrophy in lemurs has been explored in previous studies and a relationship between atrophy and intracellular amyloid deposition has been suggested [ 33 ], but this study was based on few animals. In humans, IFG is related to poor cognitive performance and to atrophy of hippocampus [ 16 17 , 19 , 34 ]. We thus assessed whether these parameters could be linked to atrophy in lemurs and found that it is probably the main factor leading to pathologic hippocampal/ septal atrophy and the associated cognitive alterations in lemurs.…”
Section: Discussionmentioning
confidence: 99%
“…IFG is a largely developed condition in middle-age healthy human [ 16 17 , 19 , 34 ]. It is related to poor cognitive performance and to atrophy of hippocampus [ 16 17 , 19 , 34 ], and concomitant to neuroinflammatory changes dependent on brain stress and NF-Kb [ 36 ]. It is thus critical to further evaluate this condition.…”
Section: Discussionmentioning
confidence: 99%
“…Is Alzheimer's a new form of diabetes? Currently, scientists report new findings linking insulin to the cognitive disorder of the brain, the correlation so strong that some researchers are calling Alzheimer's disease the new Type 3 Diabetes [10].…”
Section: Editorialmentioning
confidence: 99%
“…Shuangling Xiu et al (13) found that the elderly (community-dwelling participants aged ≥ 55 years) with impaired fasting glucose (IFG) had a lower performance on the MMSE test compared with subjects who had normal blood glucose. Jeannine S Skinner et al (14) found that high non-diabetic fasting glucose levels were associated with poorer verbal memory and executive function. However, Sai Tian et al did not find a link between fasting glucose and cognitive impairment (15).…”
Section: Introductionmentioning
confidence: 99%
“…Jeannine S Skinner et al. ( 14 ) found that high non-diabetic fasting glucose levels were associated with poorer verbal memory and executive function. However, Sai Tian et al.…”
Section: Introductionmentioning
confidence: 99%